Morphometric identification of Bursa Oynari pigeon varieties - Simsek, Ulku Gulcihan; Altundal, Burak; Akarsu, Selcukhan; Karadag, Resul (Selcuk Univ Press, 2024)
Aim: This study was carried out to make morphometric identification of male and female individuals of Karabas, Yasmakli, Muskali, Kalaca and Beyaz genotypes in Bursa Oynari pigeons. Materials and Methods: For this purpose, a total of 100 pigeons, 10 females and 10 males, 12-14 months from each genotype, were examined. Results: : The Oynar breed's average live weight was determined to be 306.27 +/- 1.32 g. Average body weights for males and females, genotypes, and gender x genotypes were discovered to be similar (p>0.05). Males were found to have longer heads (p<0.05), but there was no statistically significant difference between males and females in terms of other body traits (p>0.05). Different averages were determined in the genotypes in terms of beak length, beak depth, trunk length, body length, wing length, chest circumference, chest depth, and tail length (p<0.05). In general, the averages were lower in the Yasmakli genotype than in other genotypes, and higher in the Beyaz and Muskali genotypes (p<0.05). The interaction between gender and genotypes was significant in beak depth (p<0.001). Conclusion: As a result, it was anticipated that the characteristics detected for the first time in the Oynar breed varieties would contribute to the definition of this breed. It was also estimated that differences in the body structures of the varieties may impact their flight characteristics, and the findings on this subject will attract the attention of pigeon breeders. Considering their body structures, it was determined that the Kalaca, Muskali, and Beyaz genotypes may have superior characteristics in terms of flight time, and the Yasmakli genotype may have superior characteristics in terms of flight speed.